Pengaruh Perilaku Motivasi dan Literasi Keuangan Terhadap Keputusan Mahasiswa Berinvestasi di Pasar Modal Syariah - Nurjanah; Putri Syahrani; Shelly Midesia (Jurnal Investasi Islam, 2024)
This research aims to determine the influence of motivational behavior and financial literacy on FEBI IAIN Langsa students' decisions in investing. The method used is a quantitative approach. This research uses probability sampling using simple random sampling. The sample used was 59 FEBI IAIN Langsa students. The data collection technique uses a questionnaire. The data analysis method uses multiple linear regression, classical assumption tests, and hypothesis tests (t test, F test and R2). The results of the t test research show that the independent variable motivational behavior has a significant positive effect on stock investment decisions among FEBI IAIN Langsa students with a t value of 2.852 > 1.672 and sig 0.049 < 0.05 and financial literacy has a significant positive effect on stock investment decisions among FEBI IAIN Langsa students with a t value of 5.032 > 1.662 and sig 0.000 < 0.05. The results of the F test research show that there is a positive and significant influence simultaneously between the variables of motivational behavior and financial literacy on stock investment decisions among FEBI IAIN Langsa students with an Fcount value of 64.646 > ftable 2.71.